Efektifitas Komunikasi Unit Corporate Communication Yakes Telkom Melalui Media Sosial terhadap Kebutuhan Informasi Konsumen - Fuadi, Fairuz Zahra; Lestari, Martha Tri (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2023)
Conveying information needs digitally, of course, must have effects that can help consumers to get information, especially about health, so this research was conducted to find out the Communication Effectiveness of Yakes Telkom's Corporate Communication Unit through Social Media on Consumer Information Needs. By having a research objective to obtain the level of strength of the relationship between the independent variables, namely the effectiveness of communication and social media on the dependent variable, namely information needs. This research uses quantitative research methods with descriptive analysis research types. For sampling, the non-probability sampling method was used with 357 consumers of Yakes Telkom. The analysis technique used by the researcher is descriptive and multiple linear regression analysis. From the results of hypothesis testing, the effectiveness of communication and social media has a significant influence on consumer information needs. This is evidenced by the partial results of the Hypothesis Test (T-test) and it is found that the effectiveness of communication has a significant effect on information needs besides that social media also influences consumer information needs. The results of the test for the coefficient of determination show that the overall data for the two variables of communication effectiveness and social media have a fairly good influence on the variable consumer information needs. This study concludes that the two variable aspects have a good influence on the information disseminated by the Yakes Telkom Corporate Communications Unit. Keywords: Communication Effectiveness, Social Media, Consumer Information Needs, Yakes Telkom.